Postmenopausal Hormone Replacement Therapy - A Review - Dr. SANGEETA BHANWRA (International Journal of Pharma and Bio Sciences, 2010)
Postmenopausal Hormonal Replacement Therapy (HRT) can improve the symptoms like hot flushes,night sweats,insomnia and vaginal dryness, if given for short term. Long team disabilities of osteoporosis can be prevented by giving HRT for long duration. But long term usage of HRT is associated with risks like endometrial cancer and breast cancer .Venous thromboembolism and cardiovascular risks are also found to be increased with its use. So ,to use or not to use HRT is one of the most complex and difficult healthcare decisions and should be made ,weighing all the benefits and risks, that too on a short time basis. Life style changes, such as increasing physical activity, smoking cessation and maintaining a healthy diet and emotional support of family may be helpful in controlling symptoms and preventing chronic disease. These days use of alternative therapies like SERMs and STEARs is upcoming which may substitute HRT in some patients.